2013
DOI: 10.1097/fjc.0b013e318291c094
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 Attenuates Doxorubicin-induced Autophagy in Neonatal Rat Cardiomyocytes

Abstract: Recombinant human neuregulin-1 (rhNRG-1) improves cardiac function in animal models of doxorubicin (DOX)-induced cardiomyopathy, but the underlying mechanism remains largely unknown. Here, we confirm a role for rhNRG-1 in attenuating DOX-induced autophagy and define the signaling pathways through which it mediates some of its effects. Neonatal rat ventricular myocytes were subjected to different treatments both to induce autophagy and to determine the effects of rhNRG-1 on the process. The rhNRG-1 inhibited DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Furthermore, GGF2 exposure produced a twofold increase in Bcl-2 gene expression, a response that contributes to pro-survival signaling. Bcl-2 protein expression was also observed to be upregulated in neonatal rat ventricular myocytes after rHNrg1 treatment [30] and our findings corroborate that observation. The BH3 domain-only apoptosis sensitizer protein BAD, sequesters antiapoptotic molecules like Bcl-2 and prevents them from exerting their anti-apoptotic effects [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, GGF2 exposure produced a twofold increase in Bcl-2 gene expression, a response that contributes to pro-survival signaling. Bcl-2 protein expression was also observed to be upregulated in neonatal rat ventricular myocytes after rHNrg1 treatment [30] and our findings corroborate that observation. The BH3 domain-only apoptosis sensitizer protein BAD, sequesters antiapoptotic molecules like Bcl-2 and prevents them from exerting their anti-apoptotic effects [31].…”
Section: Discussionsupporting
confidence: 90%
“…Inhibition of Bcl-2 expression using siRNA was found to have effects similar to inhibition of erbB2 which increases susceptibility to doxorubicin toxicity [30]. Our studies extend these findings to show that the type II NRG-1 isoform GGF2 also mediates activation of the erbB pathway and produces a cardioprotective effect dependent on pAKT formation.…”
Section: Discussionsupporting
confidence: 69%
“…NRG1, one of the most active members of the epidermal growth factor (EGF)-like family, encodes a membrane glycoprotein that mediates cell-cell signaling and plays a critical role in the growth and development of multiple organ systems [24]. An et al [25] reported that NRG1 can inhibit doxorubicin-induced autophagy via multiple signaling pathways to prevent further damage from cardiomyopathy. Previous studies have demonstrated that NRG1 plays an important role in aspects of glioma development and progression, including cell survival, migration, proliferation, and metastasis [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that caspases can cleave Becn1, destroying its pro-autophagic function. [68] Once Becn1 is cleaved, the C-terminal fragment is formed with a newly acquired function to amplify mitochondrial-mediated apoptosis. The BH3 domain of Becn1 showed no pro-apoptotic activity and remained within the N-terminal fragment.…”
Section: The Effect Of Doxorubicin On the Caspase Familymentioning
confidence: 99%
“…It has been shown that caspases can cleave Becn1, destroying its pro‐autophagic function . Once Becn1 is cleaved, the C‐terminal fragment is formed with a newly acquired function to amplify mitochondrial‐mediated apoptosis.…”
Section: The Effect Of Doxorubicin On the Caspase Familymentioning
confidence: 99%